2012
DOI: 10.1080/17290376.2012.683579
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with HIV infection among young persons aged 15–24 years: Evidence from an in-depth analysis of the 2005–06 Zimbabwe Demographic and Health Survey

Abstract: This study focuses on factors that predispose young persons aged 15-24 years in Zimbabwe to infection from HIV. Using the Mosley and Chen framework, multivariate modelling was used to assess the effect of demographic, socio-economic and behavioural factors on the risk of HIV infection among this target group. The study utilised data from the Zimbabwe Demographic and Health Survey (ZDHS) conducted in 2005-06. Only the variables that were significant in the bivariate analysis were included in the multivariate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 13 publications
2
19
0
17
Order By: Relevance
“…Young persons who engage in early sexual relationships are likely to have more sexual partners than their counterparts whose sexual debut occurs later predisposing them to contracting HIV and other STIs. This observation is consistent with findings from Zimbabwe which observed that a younger coital debut was associated with an increased likelihood in HIV infection compared to a later coital debut [39]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Young persons who engage in early sexual relationships are likely to have more sexual partners than their counterparts whose sexual debut occurs later predisposing them to contracting HIV and other STIs. This observation is consistent with findings from Zimbabwe which observed that a younger coital debut was associated with an increased likelihood in HIV infection compared to a later coital debut [39]. …”
Section: Discussionsupporting
confidence: 92%
“…The overall results showed that HIV risk was higher among currently and previously married individuals, low circumcision rates and high-risk sexual behaviours. These findings are consistent with those observed in previous studies based on DHS data [12,14,17,39,41,44]. A possible explanation for increased likelihood for HIV infections among divorced/separated individuals could be that previously married individuals tend to have more sexual partners than single or married individuals [45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, beyond 14 y, female adolescents have much higher HIV incidence and prevalence as compared to males (7,8,(59)(60)(61) ( Table 1). Pregnant adolescent females (46,47), adolescents with early sexual debut, married, or partnered but living separately, engaging in transactional sex, especially in rural areas (62,63), having multiple or older sexual partners (59,60,64), and those experiencing high mobility and labor migration (65,66), have also been identified to be at increased risk of HIV infection and unfavorable outcomes. Lastly, the significant proportions of perinatally-infected individuals surviving into young adolescence and young adulthood should not be overlooked (51,61,67).…”
Section: Enabling Strategies and Interventions To Improve Adolescent mentioning
confidence: 99%